Study of Educational Intervention for Malnutrition Prevention in Children Aged 9–24 - Uvarani, B.; Visithra, K. (Journal of Neonatal Surgery, 2025)
One of the key public health issues in India is malnutrition among children under the age of two years. Growth monitoring is an important method to early detect and prevent malnutrition but its application is still very low because of low maternal awareness. The aim of the study was to determine the image of growth monitoring and gauge the impact of an educative intervention on maternal knowledge and child malnutrition among mothers of children aged 9 to 24 months who visit the immunization OPD in a tertiary care hospital in Hyderabad, Telangana. Quasi-experimental pre-test and post-test design that included a control group was used. Purposive sampling was used to choose 630 mothers, 310 in the experimental group and 320 in the control group. Structured questionnaires were used in the collection of data relevant to the determination of maternal knowledge, maternal perception and child nutritional status. The intervention involved educational sessions created in PowerPoint and nutritional counseling. The data were analyzed with the help of descriptive and inferential statistics (t-tests, Chi-square). There was a demographic and environmental similarity at the baseline of the two groups. In the experimental group, knowledge scores (mean difference 9.2 to 17.5, p < 0.001), positive view of growth monitoring (35 to 74%, p < 0.001) and child malnutrition scores (mean difference 2.3 to 1.7, p < 0.001) also improved significantly post-intervention. There existed significant associations between maternal education, ANC attendance and the level of knowledge/perceptions. The educational intervention proved to be very useful in enhancing maternal knowledge and alleviating malnutrition among under-five children. An appropriate strategic move can be integrating targeted educational programs into immunization services to enhance growth monitoring and prevention of malnutrition in early childhood.